优学院: 计算u (3-t) u (t)= ( )
举一反三
- 计算u(3-t)u(t)=( ) A: u(t)-u(t-3) B: u(t) C: u(t)-u(3-t) D: u(3-t)
- 计算卷积t[u(t)-u(t-2)]*δ(1-t)的结果为()。 A: -t[u(-t)-u(-t-2)] B: (1-t)[u(t)-u(t-2)] C: (t-1)[u(t-1)-u(t-3)] D: (1-t)[u(t-1)-u(t-3)]
- 【单选题】f(t)=u(t)-u(t-1),那么f(t)*f(t)=()。 A. t[u(t)-u(t-1)]-(t-2)[u(t-1)-u(t-2)]; B. u(t)t-(t-2) [u(t-1)-u(t-2)]; C. t[u(t)-u(t-1)]- [u(t-1)-u(t-2)]; D. [u(t)-u(t-1)]- [u(t-1)-u(t-2)].
- u (5-t) u (t)= : A: u (t)- u (t-5) B: u (t) C: u (t)- u (5-t) D: u (5-t)
- 已知[img=140x25]1803567cdbdb257.png[/img],则二阶导数[img=39x26]1803567ce528242.png[/img]= ________________。 A: 3-9sin(3t)u(t) B: 3δ(t)-9sin(3t)u(t) C: 3δ(t)+9sin(3t)u(t) D: 3+9sin(3t)u(t)